Innovation in Qur'an and Hadith Learning at the Elementary Level Using the Mimicry-Memorization Method - Shilvi Salsabila, Luthfia; Handoko, Gatot (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2024)
The development of education in Indonesia is required to be able to produce a good education system and must be implemented, especially in religious learning. However, there are still religious subjects whose scores are still classified as below average such as Al-Qur'an Hadith lessons in MI Al-Hidayah Malang, the average KKM limit is> 75 or with a percentage of 75% complete. With this problem, researchers want students whose scores increase with the application of the Mimicry Memorization Method. The purpose of this study is to increase student activeness in learning Al-Qur'an Hadith and improve student learning outcomes in Al-Qur'an Hadith class 6B at MI Al-Hidayah Malang in the 2023-2024 academic year. This type of research is a Classroom Action Research (PTK) by following the Kemmis and Mc Taggart model. Classroom Action Research is carried out with 2 Cycles, which include Planning, Implementation, Observation, and Reflection. The application of the Mimicry Memorization learning method can increase student learning activeness in learning Al-Qur'an Hadith, namely in the first cycle the results of student activeness reached 60.65%, then increased in the second cycle, namely 82.87%. 2). This has actually reached the percentage of completeness, but the researcher wants to strengthen his findings again by continuing the action in the second cycle with even more increased learning outcomes of 91.60%. Based on the results of the study, it is concluded that the Mimicry M technique can be used to improve learning outcomes.